2008
DOI: 10.3748/wjg.14.6376
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cell adhesion molecule CD44 in gastric adenocarcinoma and its prognostic importance

Abstract: used for histological evaluation, including the type (Lauren's classification) and grading of the tumor. The expression of CD44 in the gastric adenocarcinoma mucosa and the adjacent mucosa were determined by immunohistochemistry. The survival analysis was obtained using the Kaplan-Meier test. RESULTS: Of 100 patients, 74 (74%) patients were male. The tumors were categorized as intestinal type (78%) or diffuse type (22%). Sixty-five percent of patients were CD44-positive. CD44 expression was not detected in nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 27 publications
2
37
2
1
Order By: Relevance
“…However, in the present study, nested RT-PCR was combined with immunohistochemical analysis of 76 cases of gastric carcinoma and 12 cases of atypical hyperplasia. The positive rate of CD44v reported using nested RT-PCR in the present study was significantly higher than the positive rates detected in previous studies (9,10,25,30), however, the possibility of false positives was not considered. Furthermore, the use of RT-PCR with nested PCR as opposed to Southern blot hybridization resulted in experimental results that were confirmed by DNA sequencing.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…However, in the present study, nested RT-PCR was combined with immunohistochemical analysis of 76 cases of gastric carcinoma and 12 cases of atypical hyperplasia. The positive rate of CD44v reported using nested RT-PCR in the present study was significantly higher than the positive rates detected in previous studies (9,10,25,30), however, the possibility of false positives was not considered. Furthermore, the use of RT-PCR with nested PCR as opposed to Southern blot hybridization resulted in experimental results that were confirmed by DNA sequencing.…”
Section: Discussioncontrasting
confidence: 55%
“…Furthermore, abnormal expression of CD44 mRNA was determined to be relatively high irrespective of whether the gastric carcinoma tissues were highly or poorly differentiated (24,25). A number of studies have proposed that the role of CD44v in enhancing the infiltration and metastasis of tumor cells may be associated with its ability to alter the structure and function of cell surface adhesion molecules (10,26). Miwa et al (27) revealed that gastric carcinoma tissues exhibited higher CD44v expression compared with that of adjacent healthy tissues, with 76.6% (23/30 cases) positive expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, most reports described the expression of CD44 variants and their association with the distinct histotypes of this neoplasia in comparison with normal mucosa, without further considerations. [15][16][17][18][19][20] In this study we aimed to dissect the splicing pattern of CD44 in gastric neoplasm in comparison to normal stomach. The expression of relevant splicing forms was further quantified and compared with that of normal gastric mucosa, in terms of RNA and protein, in distinct lesions and stages of GC development: GC cell lines, primary premalignant lesions and malignant gastric lesions (sporadic and hereditary forms).…”
mentioning
confidence: 99%
“…In gastric adenocarcinoma, CD44 is highly expressed and is correlated with a poor prognosis in patients with the intestinal disease type (44). In a previous study, we reported that the regulation of matrix metalloproteinase-9, intercellular adhesion medlecule-1 and E-Cadherin expression may be one of the potential molecule mechanisms for IL-8-induced adhesion, migration and invasion in gastric cancer (16).…”
mentioning
confidence: 99%